Prévalence et causes de la cécité au Congo. - Négrel, A. D. (World Health Organization, 1990)
A population-based survey on the prevalence of blindness and eye disease has been conducted throughout the Congo. This was the first time such a survey had been carried out in a central African country with an equatorial climate. In comparison with data available from other African countries, the two rather unexpected characteristics resulting from the survey were lower blindness prevalence rates and the extremely rare cases of bilateral corneal scarring. In accordance with sampling procedures recommended by the WHO Programme for the Prevention of Blindness, 7041 people were selected and examined. The prevalence of blindness (visual acuity less than 3/60 in the better eye) was 0.3% (5700 people). The prevalence of low vision (visual acuity between 6/24 and 3/60 in the better eye) was 2.1% (40,000 people). The major causes of blindness and low vision were cataract (81% and 80%, respectively) and glaucoma (9% and 3.4%, respectively). A total of 22,000 people in the Congo require cataract surgery. Almost four-fifths of the current burden of blindness in this country is potentially curable through the provision of cataract surgery and aphakic glasses.